PARAMETRIC ANALYSIS OF FLOATING SOLAR SYSTEM FOR MALAYSIAN OFFSHORE APPLICATIONS - Xiang En, Roy Chang (Universiti Teknologi PETRONAS, 2020)
Non-renewable energy like Coal, and Natural Gas was the main source to generate electricity in Malaysia. These energies were unquestionable important for Malaysia as it powered the whole nation. Unfortunately, these energies brought a significant negative impact on the environment like Greenhouse Effect, Climate Change, Acid Rain, and Global Warming. As the depletion and the negative impact of non-renewable energy, the Malaysian government has chosen an alternative which was renewable energy. Solar energy was one of the rising popularities of renewable energy in the globe, not to mention in Malaysia. Plus, Malaysia has a high potential in developing solar energy because of the high sunlight intensity. Though Malaysia has not achieved enough knowledge and experience in constructing a floating solar farm at an open sea, detailed research was needed to ensure the performance of the offshore floating solar platform.